MPP+ disorders Irg1-Itaconate axis to promote M1 polarization of microglia by activating succinate dehydrogenase - Lin-Yu Wang; Yi-Yun Tang; Wei Zou; Ping Zhang; Xiao-Qing Tang; Ping Zhang (Molecular Biology Reports, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Ecological connectivity of phytoplankton community in the Xincun Bay lagoon, Hainan Island - Jian Zou; Yayuan Xiao; Lin Lin; Peng Wu; Teng Wang; Yu Liu; Shannan Xu; Yong Liu (Journal of Marine Systems, 2026)

Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

Exogenous organic matter and clay mineral additions regulate microbial-mineral mediated soil organic carbon accumulation in alkaline-calcareous soils - Xi Yang; Donghao Ma; Lin Chen; Ting Yang; Yongqi Zhang; Hongwei Jiang; Nan Zhang; Hongtao Zou; Congzhi Zhang; Guixiang Zhou; Yanfang Zhou; Yu Luo; et al. (Applied Soil Ecology, 2026)

Ultra-high pressure-assisted enzymatic extraction enhances phenolic release and functional potency in fermented dark tea extracts - Xiaoying Lin; Jun Li; Yuanshan Yu; Dengwen Lei; Tenggen Hu; Manqin Fu; Qiang Xiao; Junying Zou; Ya Gao; Chao Huang; Jing Wen (Food Research International, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Longitudinal trends in serum triclocarban levels from 2008 to 2018: Evidence from the prospective Dongfeng–Tongji cohort study - Caizheng Yu; Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Meian He (Environmental Research, 2026)

ANN-assisted interfacial engineering of MOFs heterostructures for synergistic CO2 photoreduction and antibiotic elimination - Fan Ye; Zhe Lin; Xu-Chao Xia; Ting Zou; Jin-Yu Dai; Lin Zhang; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2026)

Ethylene signaling, pathogenesis-related proteins (PRs) and SlCBF1 collectively regulate Botrytis cinerea resistance in postharvest tomato fruit under low temperature conditions - Pan Shu; Zhiyuan Wang; Bingqing Qian; Zhiyin Yu; Qinlu Zheng; Xin Yao; Hongye Fu; Yuan Qing; Xiaojuan Yin; Pan Zou; Jing Li; Lin Shen (Postharvest Biology and Technology, 2026)

In-situ heterojunction on high-aspect-ratio cellulose nanocrystals for long-range charge transport in e-skin - Chenchen Shen; Weiwei Chen; Lin Guo; Yanrui Zou; Shuan Han; Ning Yu; Lin Gan; Jin Huang (Carbohydrate Polymers, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Hierarchically assembled UiO-66@PIL@PP core-shell catalyst: Synergistic integration of catalysis and CO2 enrichment for efficient cycloaddition - Zhenzhu Tang; Qian Zhang; Baowen Lin; Yunliang Yu; Yanbin Zeng; Chao Zou; Guanqun Xie; Xiaoxia Wang (Journal of Environmental Chemical Engineering, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

Characterization of the ctgf Promoter from Nibea coibor and its Response to TGF-β1 During Collagen Synthesis in Swim Bladder Cells - Ailing Zou; Yuying Yuan; Lingling Zhu; Yu Zhang; Lanfei Xiao; Xiaobo Wen; Fan Lin (Marine Biotechnology, 2026)

Acupuncture improves neurological function in ICH rats via suppression of WNK-SPAK-NKCC1 signaling activation - Bai-Wen Zhang; Lei Zheng; Bing-Lin Kuang; Jia Zheng; Xue-Ping Yu; Xiao-Hong Dai; Wei Zou (Journal of Molecular Histology, 2026)

Anomaly analysis and comprehensive evaluation of geochemical exploration for oil and gas in the Lindian area, Northern Songliao Basin - Xiaohui Lin; Fazhun Rong; Kewei Xu; Yu Zou; Wu Li; Yinjie Chen (Geosciences Journal, 2026)

Three-dimensional hierarchical CuCoAl-layered double hydroxide/Ti3C2 Schottky heterojunction for efficient visible-light degradation of ciprofloxacin - Zifei Gao; Ye Liu; Deke Wang; Baoyu Zou; Xingkang Yu; Yu Dong; Qing Li; Juanjuan Ma; Lin Liu; Chao Liu; Zhiwei Tong; Jun Hu (Applied Clay Science, 2026)

Evaluation of different types of isotope-labelled steroids based on liquid chromatography–mass spectrometry - Yameng Zhao; Luqi Sun; Pengshuai Zhang; Sen Xu; Shenghao Zhu; Lantao Zhang; Mingyang Hu; Jinglan Yu; Zhaocong Shang; Lin Zou; Wen Lei (Isotopes in Environmental and Health Studies, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

Data-driven reduced-order prediction modeling for cylinder vortex-induced vibrations in the subcritical Reynolds number regime - Jingyuan Wang; Li Zou; Guoqing Jin; Zongbing Yu; Maoyue Lin (Ocean Engineering, 2026)

Cation-anion synergistic interactions in ion-regulated cholesteric liquid crystal Hydroxypropyl methylcellulose coatings for lithium metal batteries - Zhanpeng Du; Yun Huang; Fengliang Wang; Lei Zhang; Jing Tao; Jin Bao; Heguo Zeng; Jiajun He; Huihui Li; Chao Zou; Chunmei Feng; Bingshu Guo; et al. (Chemical Engineering Journal, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

Exposure trends of neonicotinoids from 2008 to 2018 and health risk in a longitudinal study in China - Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Caizheng Yu; Meian He (Environmental Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Bioengineered functional scaffolds co-loaded with osteonectin and HA-internalizing osteoblasts for boosting bone regeneration - Wei Yang; Qin Zou; Chenxin Wang; Yuankun Ren; Rui Zhang; Mingyue Lin; Xueqi Zhang; Yu Liu; Boyang Wang; Wei Li; Li Jiang; Xiyu Li (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Constructing Ce–O–C covalent-bridged S-scheme heterojunction via molten-salt transformation of Ce-MOF for photocatalytic overall H2O2 synthesis - Ziying Feng; Pengjia Li; Dou Yang; Jingyi Yu; Yunyun Gui; Shao-Chuan Li; Yuan Lin; Junhua Zou; Lijun Liu (Journal of Environmental Chemical Engineering, 2026)

Water quality and biofilm growth in drinking water distribution systems with the low-dose sodium hypochlorite disinfection after ultrafiltration pretreatment - Yu Zhou; Kangbing Zou; Xiaokai Wang; Zhihong Wang; Wei Song; Xing Du; Dachao Lin (Journal of Environmental Sciences, 2026)

Bacillus and lactic acid bacteria inoculation to transform kitchen waste using Hermetia illucens - Guoyou Deng; Min Yan; Shengzhi Yang; Lin Ji; Xinfeng Han; Xiumei Yu; Ke Zhao; Likou Zou (Journal of Environmental Sciences, 2026)

Effect of oxygen-containing functional groups on selenium removal by the carbonaceous adsorbent from MSW incineration flue gas - Shuaijie Yu; Shuai Li; Hongyun Hu; Linxia Gao; Zhong Lin; Chan Zou; Lu Dong; Yongda Huang; Hong Yao (Fuel, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

Radioactivity of 14C, OBT, and TFWT in seafood from coastal areas of Zhejiang Province: Assessment of internal exposure to the public - Hong Ren; Kaiwen Tan; Feng Lin; Taotao Zheng; Xiaoxiang Ma; Peng Wang; Shunfei Yu; Hua Zou; Xinyu Gong; Yiyao Cao (Food Control, 2026)

A facile and sensitive protein immune polyacrylamide gel electrophoresis with online fluorescent imaging - Rui Zou; Zixian Yu; Jing Gao; Qiang Zhang; Yiren Cao; Xiaoyi Lin; Yibing Peng; Weiwen Liu; Jianguang Wu; Chengxi Cao (Analytica Chimica Acta, 2026)

Interfacial adsorption mechanism of a novel sodium morpholine dithiocarbamate depressant in selective flotation separation from chalcopyrite and molybdenite - Song Zou; Yue Lin; Zhiqiang Huang; Xinyang Yu; Guichun He (Minerals Engineering, 2025)

A pH-responsive and nitric oxide-producing nanocarrier for targeted therapy of melanoma - Shuai Cui; Qing Yu; Ziyuan Su; Yiting Han; Sujuan Wang; Xiangyu Zou; Lin An; Nannan Yin; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Correction: Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2025)

Biogeochemical responses to the dynamic processes associated with the Equatorial Undercurrent in the tropical eastern Indian Ocean during April–May - Qinsheng Wei; Huiwu Wang; Yongliang Duan; Junchuan Sun; Teguh Agustiadi; Xiaomeng Duan; Yawen Zou; Lin Liu; Baodong Wang; Weidong Yu (Acta Oceanologica Sinica, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Urea-engineered magnetic ZnFe2O4/Bi2S3 heterojunction for SPC-activated photocatalytic Fenton-like degradation of sulfadiazine - Junge Xu; Haoying Guo; Dong Wang; Yanfang Li; Yuan Lin; Weihao Yu; Yingmu Wang; Rusen Zou; Xiaoping Gao; Baoling Yuan (Chemical Engineering Journal, 2025)

Hollow p-n heterostructures with vacancy engineering to enhance Z-scheme photocatalytic CO2 reduction - Zhitao Zou; Yaxin Wang; Tianyi Zhang; Jing Lu; Vladimir Turkevich; Yueqin Yu; Jixiang Xu; Haifeng Lin; Yanyan Li; Lei Wang (Chemical Engineering Journal, 2025)

Cellulose nanocrystal-modified hydrogel wearable sensor with self-healing function from dynamic bond and controllable dual hydrogen-bond crosslinking - Ruihuan Gu; Weiwei Chen; Yanrui Zou; Tingting Yang; Zirui Liu; Ning Yu; Jin Huang; Lin Gan (Carbohydrate Polymers, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Distribution of and associations between ARGs and pathogenic bacteria in soils affected by heavy metal contamination in mining areas - Yanbin Du; Yijia Liu; Caihong Yu; Xuesong Hu; Suya Ma; Jiacheng Zou; Ronghua Lin; Yanhua Hou; Menglun Wang; Nan Zhang (Journal of Environmental Chemical Engineering, 2025)

Estimation of rice yield using multi-source remote sensing data combined with crop growth model and deep learning algorithm - Jian Lu; Jian Li; Hongkun Fu; Wenlong Zou; Junrui Kang; Haiwei Yu; Xinglei Lin (Agricultural and Forest Meteorology, 2025)

Corrigendum to “Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis” [Toxicology and applied Pharmacology, 2023, 462:116415] - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2025)

Gut microbiota and metabolic functions in herbivorous fish from Xisha coral reefs, China - Xiyue Yang; Yayuan Xiao; Xiaojun Shi; Tuanjie Li; Xiaofei Xiong; Teng Wang; Lin Lin; Yu Liu; Jian Zou; Chunhou Li; Yong Liu; Peng Wu (Marine Environmental Research, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In-situ reconstruction of active bismuth for enhanced CO2 electroreduction to formate - Chenchen Weng; Cheng Wang; Yang Song; Yu-Xiao Zhang; Kang Zou; Hongwu Chen; Xue Yang; Wei Lin (Chemical Engineering Journal, 2025)

Enhancing porcine oocyte quality and embryo development through natural antioxidants - Zheng Feng; Jia Song; Chenghong Lin; Siyu Wu; Yu Wang; Qingyuan Hui; Yinting Pan; Yiman Zou; Chaofeng Zeng; Jinbiao Guo; Yangli Pei (Theriogenology, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

Phosphine oxide functionalized porous aromatic frameworks enabled wireless bionic olfactory system with preconcentration capability for trace ammonia monitoring - Shuai Zhao; Hongyang Jin; Zihao Chen; Yonglai Zhang; Xiaoqin Zou; Lin Xu; Shaolei Wang; Zhenglei Yu; Zhiyong Chang (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

A comprehensive review of microplastic aging: Laboratory simulations, physicochemical properties, adsorption mechanisms, and environmental impacts - Yu Gao; Wei Gao; Yuzhi Liu; Donglei Zou; Yuan Li; Yingzi Lin; Jun Zhao (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Enhanced mass scattering efficiencies of background dust aerosols over East Asia following the passage of dust plumes - Chenguang Tang; Yingjing Lin; Pengfei Tian; Jinsen Shi; Tao Deng; Xuejiao Deng; Yu Zou; Lei Zhang (Atmospheric Environment, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Pure water and resource recovery from municipal wastewater using high-rate activated sludge, reverse osmosis, and mainstream anammox: A pilot scale study - Haoran Zhao; Yu Zhou; Lianpei Zou; Chihao Lin; Jianyong Liu; Yu-You Li (Water Research, 2024)

Synergistic effects of metallic IrCo for promoted nitrate reduction in industrial-relevant wastewater level - Yu Tang; Pan Ran; Linjun Zhong; Haohong Liao; Qing Tong; Weixin Zou; Lin Dong (Chemical Engineering Journal, 2024)

Correction to: A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

Ensuring Clinical Excellence: The Mindray SAL9000 Biochemical Immunoassay System - Zhenzhen Zou; Honghui Tang; Erya Xiao; Yu Zhou; Xuebei Yin; Zhen Hu; Yang Cai; Qingzhen Han; Lin Wang (Cell Biochemistry and Biophysics, 2024)

Dynamic Response Prediction Model for Jack-Up Platform Pile Legs Based on Random Forest Algorithm - Xiaohui Cui; Hui Liu; Xiang Lin; Jiahe Zou; Yu Wang; Bo Zhou (Journal of Marine Science and Engineering, 2024)
Jack-up offshore platforms are widely used in many fields, and it is of great importance to quickly and accurately predict the dynamic response of platform pile leg structures in real time. The current analytical techniques are founded upon numerical modelling of the platform structure. Although these methods can be used to accurately analyze the dynamic response of the platform, they require a large quantity of computational resources and cannot meet the requirements of real-time prediction. A predictive model for the dynamic response of the pile leg of a jack-up platform based on the random forest algorithm is proposed. Firstly, a pile leg dynamic response database is established based on high-fidelity numerical model simulation calculations. The data are subjected to cleaning and dimensional reduction in order to facilitate the training of the random forest model. Cross-checking and Bayesian optimization algorithms are used for the selection of random forest parameters. The results show that the prediction model is capable of outputting response results for new environmental load inputs within a few milliseconds, and the prediction results remain highly accurate and perform well at extreme values.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Insight into simultaneously sludge dewatering and antiviral drugs removal by integrated particle electrodes assisted electrochemical oxidation - Haixiang Yu; Yiyang He; Hong Tao; Haiping Yuan; Feiyan Wu; Rusen Zou; Suyun Xu; Lin Gu (Journal of Environmental Chemical Engineering, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Unified stress–strain calculation model for UHPC-filled stainless-steel tubular columns with various cross-sectional shapes under axial compression - Zhuang Zhao; Yang Wei; Xingxing Zou; Dongdong Chen; Yu Lin; Kaiqi Zheng (Engineering Structures, 2024)

Sleep onset time as a mediator in the association between screen exposure and aging: a cross-sectional study - Senlin Lin; Meng Gao; Juzhao Zhang; Yuting Wu; Tao Yu; Yajun Peng; Yingnan Jia; Haidong Zou; Lina Lu; Deshang Li; Yingyan Ma (GeroScience, 2024)
Excessive screen exposure has become a significant health concern. This study investigates the impact of screen time on aging in middle-aged and elderly populations. Healthy working adults over 45 years old in Shanghai, China, underwent general and ocular examinations. Questionnaires collected demographics, medical history, and screen exposure details. Aging was assessed using the retinal age gap, defined as the difference between the retinal age predicted by deep learning algorithms based on fundus images and chronological age. Pathway analysis tested the mediation effect of sleep duration and onset time on the relationship between screen usage and retinal age gap. The retinal age gap increased with longer screen exposure, from 0.49 ± 3.51 years in the lowest tertile to 5.13 ± 4.96 years in the highest tertile (Jonckheere-Terpstra test, p < 0.001). Each additional hour of screen exposure accelerated the retinal age gap by 0.087 years (95% CI, 0.027, 0.148, p = 0.005) in the fully adjusted linear model. Sleep onset time mediated the impact of screen usage on the retinal age gap (indirect effect, β = 0.11; 95% CI 0.04–0.24). The impact of screen usage in a light-off environment on the retinal age gap was fully mediated by sleep onset time (indirect effect, β = 0.22; 95% CI 0.07–0.38), with the proportion being 100%. Our study identified a correlation between excessive screen time and a wider retinal age gap in middle-aged and elderly individuals, likely due to delayed sleep onset. To mitigate the adverse effects on the retina and aging, it is important to limit screen usage and avoid screens before bedtime.

A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

IFNγ modulates the innate immune response via Toll-like receptors in green-spotted pufferfish (Tetraodon nigroviridis) - Wenjie Lai; Qinxi Dai; Zhenjiang Zou; Ziyi Wu; Ting Wang; Xue Yu; Yakang Song; Jingpeng Hou; Yuyou Lu; Dingrui Liu; Haoran Lin; Yong Zhang; et al. (Aquaculture International, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Immune-enhancing activity of compound polysaccharide on the inactivated influenza vaccine - Yang Zhang; Depeng Wang; Daotong Tan; Anqi Zou; Zhe Wang; Hao Gong; Yu Yang; Lishan Sun; Xiaoliang Lin; Ming Liang; Yi Yu; Xiaoxi He; et al. (Carbohydrate Polymers, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Metal-phenolic nanocatalyst rewires metabolic vulnerability for catalytically amplified ferroptosis - Yang Zhu; Xuegang Niu; Tiantian Wu; Junjie Cheng; Jianhua Zou; Yuanbo Pan; Yu Tian; Wei Huang; Chengyu Ding; Yuanxiang Lin; Dezhi Kang; Xiaoyuan Chen (Chemical Engineering Journal, 2024)

Long-term biogas slurry application increases microbial necromass but not plant lignin contribution to soil organic carbon in paddy soils as regulated by fungal community - Zhaoming Chen; Jinchuan Ma; Junwei Ma; Jing Ye; Qiaogang Yu; Ping Zou; Wanchun Sun; Hui Lin; Feng Wang; Xinlin Zhao; Qiang Wang (Waste Management, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Emissions from international airport and its impact on air quality: A case study of beijing daxing international airport (PKX), China - Ya-nan Wang; Chao Zou; Tian-ge Fang; Nai-xiu Sun; Xiao-yu Liang; Lin Wu; Hong-jun Mao (Environmental Pollution, 2023)

Response of topsoil Fe-bound organic carbon pool and microbial community to Spartina alterniflora invasion in coastal wetlands - Meifen Lin; Yu Chen; Liwen Cheng; Yi Zheng; Weiqi Wang; Jordi Sardans; Zhaoliang Song; Georg Guggenberger; Yuanchun Zou; Xueli Ding; Akash Tariq; Fanjiang Zeng; et al. (CATENA, 2023)

A review on recent advances in LED-based non-thermal technique for food safety: current applications and future trends - Xinpeng Yu; Peng Zheng; Yuan Zou; Zhiwei Ye; Tao Wei; Junfang Lin; Liqiong Guo; Hyun-Gyun Yuk; Qianwang Zheng (Critical Reviews in Food Science and Nutrition, 2023)

Targeted isolation of ursane-type triterpenoids from Tragopogon porrifolius based on Feature-Based Molecular Networking - Hong-bing Sun; Hai-fei Zou; Bing Xia; Yu-cheng Gu; Wen-lin Wu; Yan Zhou (Phytochemistry Letters, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

Periodate activation by atomically dispersed Mn on carbon nanotubes for the production of iodate radicals and rapid degradation of sulfadiazine - Jiahui Hu; Yubin Zou; Yin Li; Zehui Yu; Yutian Bao; Lin Lin; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2023)

Using quantum chemistry theory to elucidate the mechanism for treating sulfonamide antibiotic wastewater by progressive freezing - Zhang Yan; Liu Tong-shuai; Wang Xiao-zhuang; Liu Yu-can; Zhao Chen; Lin Hao; Zou Yi-hong (Journal of Water Process Engineering, 2023)

Hydrogen sulfide antagonizes formaldehyde-induced ferroptosis via preventing ferritinophagy by upregulation of GDF11 in HT22 cells - Yu-Hui Tang; Lei Wu; Hong-Lin Huang; Pan-Pan Zhang; Wei Zou; Xiao-Qing Tang; Yi-Yun Tang (Toxicology, 2023)

Development and optimization of LED systems for surface fungal decontamination of fresh produce - Xinpeng Yu; Weihong Deng; Ziqian Zhang; Yuan Zou; Tao Wei; Junfang Lin; Liqiong Guo; Hyun-Gyun Yuk; Zhiwei Ye; Qianwang Zheng (Postharvest Biology and Technology, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Different cold tolerances among three strains of large yellow croaker: related to antioxidant defense and energy metabolism - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Hui Zhang; Yu-Cong Huang; Wei-Guang Zou (Fish Physiology and Biochemistry, 2023)

Diffusion mechanism of deep shale gas and its carbon isotope fractionation: a combined simulated and mathematical analysis - Yu Zou; Guojian Wang; Cheng Tao; Rui Zhou; Shangqing Zhang; Dongna Liu; Xiaohui Lin; Xuying Zheng (Geosciences Journal, 2023)

Influencing pathways and toxicity changes of pre-ozonation on carcinogenic NDEA formation from greenhouse gas adsorbent DEAPA in subsequent disinfection processes - Tianze Liu; Xiaobin Liao; Xinna Lin; Jing Yu; Huan Qi; Zhibin Jiang; Jing Zou; Qingsong Li (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

A novel 4-O-endosulfatase with high potential for the structure-function studies of chondroitin sulfate/dermatan sulfate - Lin Wei; Yingying Xu; Min Du; Ying Fan; Ruyi Zou; Xiangyu Xu; Qingdong Zhang; Yu-Zhong Zhang; Wenshuang Wang; Fuchuan Li (Carbohydrate Polymers, 2023)

Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Differential responses of soil nirS- and nirK-type denitrifying microbial communities to long-term application of biogas slurry in a paddy soil - Zhaoming Chen; Jinchuan Ma; Yinxiu Liu; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Qiang Wang (Applied Soil Ecology, 2023)

Transcriptomics and metabolomics together reveal the underlying mechanism of heroin hepatotoxicity - Yingbiao Yue; Lei Zou; Jie Tao; Lin Yin; Zhenrong Xie; Yu Xia; Zunyue Zhang; Kunhua Wang; Mei Zhu (Toxicology, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

Soil moisture dynamics near a gully head in relation to the trigger of collapse in granite red soil slope in southern China - Ziqiang Zou; Yu Tao; Yuhao Gao; Zixuan Liu; Wenkai Li; Zhengchao Tian; Lirong Lin; Yangbo He; Jiazhou Chen (Geomorphology, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

K+ and CeO2 nanoparticles modified OMS-2 nanorods for enhanced activity and stability of photocatalytic toluene oxidation: K+ charge modulation and mechanistic investigation - Pingping Yu; Nan Li; Weixin Zou; Xiaoqian Wei; Jiawei Ji; Li Han; Yandi Cai; Wei Tan; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Differential responses of bacterial communities in coral tissue and mucus to bleaching - Yiyang Zou; Yu Chen; Lin Wang; Si Zhang; Jie Li (Coral Reefs, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Fate of heavy metals and bacterial community composition following biogas slurry application in a single rice cropping system - Qiang Wang; Zhaoming Chen; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Jinchuan Ma (Journal of Soils and Sediments, 2022)

Why pendulum symmetry is absent from the cymose partial inflorescences of Cannaceae? Insights into the essential characteristic of cincinni - Xueyi Tian; Qianxia Yu; Canjia Lin; Tong Zhao; Pu Zou; Jingping Liao (Journal of Plant Research, 2021)

The effect of conservation tillage in managing climate change in arid and semiarid areas—a case study in Northwest China - Lin Dong; Tong Si; Yu-e Li; Xiao-Xia Zou (Mitigation and Adaptation Strategies for Global Change, 2021)

Structural and functional brain signatures of endurance runners - Long Cao; Yuanchao Zhang; Ruiwang Huang; Lunxiong Li; Fengguang Xia; Liye Zou; Qian Yu; Jingyuan Lin; Fabian Herold; Stephane Perrey; Patrick Mueller; Milos Dordevic; et al. (Brain Structure and Function, 2021)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

A novel putative betapartitivirus isolated from the plant-pathogenic fungus Rhizoctonia solani - Yi Chen; Jia En Su; Xi Yun Qin; Zhi Yong Fan; Xiao Hai Zhang; Qing Yu; Zhen Yuan Xia; Cong Ming Zou; Gao Kun Zhao; Zhong Long Lin (Archives of Virology, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Soil microbial activity and community composition as influenced by application of pig biogas slurry in paddy field in southeast China - Zhaoming Chen; Qiang Wang; Junwei Ma; Stephen Chapman; Ping Zou; Jing Ye; Qiaogang Yu; Wanchun Sun; Hui Lin; Lina Jiang (Paddy and Water Environment, 2020)

Integrated analysis of quantitative proteome and transcriptional profiles reveals abnormal gene expression and signal pathway in bladder cancer - Songbai Liao; Minglin Ou; Liusheng Lai; Hua Lin; Yaoshuang Zou; Yonggang Yu; Xuede Li; Yong Dai; Weiguo Sui (Genes & Genomics, 2019)

Triterpenoid saponins from the buds of Lonicera similis - Xiao Zhang; Li-Hua Zou; Yu-Lin He; Cheng Peng; Li Guo; Liang Xiong (Natural Product Research, 2018)

Co-Delivery of Ciprofloxacin and Colistin in Liposomal Formulations with Enhanced In Vitro Antimicrobial Activities against Multidrug Resistant Pseudomonas aeruginosa - Shaoning Wang; Shihui Yu; Yuwei Lin; Peizhi Zou; Guihong Chai; Heidi H. Yu; Hasini Wickremasinghe; Nivedita Shetty; Junhong Ling; Jian Li; Qi Zhou (Pharmaceutical Research, 2018)

A new cycloartane triterpenoid glycoside from Souliea vaginata - Hai-Feng Wu; Xin Liu; Yin-Di Zhu; Jing Zhou; Ying-Ying Gong; Guo-Xu Ma; Xu-Dong Xu; Yi-Lin Liu; Zheng-Hong Luo; Di-Zhao Chen; Qiong-Yu Zou; Zi-Jian Zhao (Natural Product Research, 2017)

A new diphenyl ether derivative from Mirabilis himalaica - Si-Yu Zhou; Guo-Wei Wang; Yan-Lin Zou; Li-Qing Deng; Ming-Xu Liu; Zhi-Hua Liao; Xiao-Zhong Lan; Min Chen (Natural Product Research, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Effects of combined application of organic and inorganic fertilizers plus nitrification inhibitor DMPP on nitrogen runoff loss in vegetable soils - Qiaogang Yu; Junwei Ma; Ping Zou; Hui Lin; Wanchun Sun; Jianzhen Yin; Jianrong Fu (Environmental Science and Pollution Research, 2015)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

Transgenic expression of an insect diapause-specific peptide (DSP) in Arabidopsis resists phytopathogenic fungal attacks - Tingquan Wu; Yongfang Chen; Weida Chen; Shenghao Zou; Yongqing Zhang; Yu’e Lin; Zhaojun Liang; Dingzhong Tang (European Journal of Plant Pathology, 2013)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

Cloning and the expression pattern of Spätzle gene during embryonic development and bacterial challenge in Artemia sinica - Lu-ping Zheng; Lin Hou; Miao Yu; Xiang Li; Xiang-yang Zou (Molecular Biology Reports, 2012)

ADAM17 regulates prostate cancer cell proliferation through mediating cell cycle progression by EGFR/PI3K/AKT pathway - Ping Lin; Xicai Sun; Tian Feng; Haifeng Zou; Ying Jiang; Zijun Liu; Dandan Zhao; Xiaoguang Yu (Molecular and Cellular Biochemistry, 2012)

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2011)

Transgenic Amorphophallus konjac expressing synthesized acyl-homoserine lactonase (aiiA) gene exhibit enhanced resistance to soft rot disease - Huifang Ban; Xinli Chai; Yongjun Lin; Ying Zhou; Donghai Peng; Yi Zhou; Yulan Zou; Ziniu Yu; Ming Sun (Plant Cell Reports, 2009)

The timing of re-institution of good blood glucose control affects apoptosis and expression of Bax and Bcl-2 in the retina of diabetic rats - Xin-Yuan Gao; Hong-Yu Kuang; Wei Zou; Xiao-Min Liu; Hong-Bin Lin; Yi Yang (Molecular Biology Reports, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)